Garella ruficirra (Hampson, 1905) [Noctuoidea: Nolidae: Chloephorinae: Sarrothripini] Infesting Young Shoots of Quercus lanata Smith, 1819 (Fabaceae) in Kumaon region of Uttarakhand - Singh, Arun P.; Ramola, Gaurav C. (Indian Forester, 2020)
No Abstract.